The Dialogic Self: Language and Identity in Annie Ernaux - Warren Johnson (Studies in 20th & 21st Century Literature, 1999)
The nine largely autobiographical texts that Annie Ernaux (1940- ) has published to date, which range stylistically from early strident outpourings to the willed transparency of an "écriture plate," all reveal the narrator as a patchwork subjectivity comprised of the discourses surrounding the child, adolescent, and adult against which she reacts, frequently without comprehending her own motivations. I try to unravel the strands that make up Ernaux's language and explore how the self that emerges is an aggregate of the discursive spaces she has inhabited. I trace as well how her gender identity impacts her capacity and willingness to struggle against these various ideologically inflected languages. If the narrator's attempt to be independent of the formative forces surrounding her turns out to be misguided, the effort has not been wasted, for it has furnished a strikingly vivid account of the struggle of the individual to achieve an awareness, denied to her parents and other inhabitants of her socially marginal milieu, of the possibilities that open up through entry into the spheres of other languages.
Keywords: Annie Ernaux; child; adolescent; author intent; language; self; space; discursive space; French literature